APLIKASI PRINSIP SYARIAH HOTEL SOFYAN INN BANDUNG: Analisis terhadap penerapan prinsip syariah di hotel Sofyan Inn Specia Bandung - Setia Permana W, Irfan (Penerbit CV Tentrem Karya Nusa, 2019)
This paper is expected to know about the principles of sharia business that is the principle of monotheism, balance, caliph (leadership), and justice, and know how the application of sharia principles in aspects of product, service, and management at Hotel Sofyan Inn Specia. This research uses field research type with qualitative research approach, data collection with library research, interview and observation. Data analysis using descriptive analysis with the aim of describing the data that the author collects about the application of sharia principles. This study concludes that Sofyan Inn Specia Hotel applies the principles of Tawheed, balance (tawazun), khilafah (leadership), and al-'adl (justice) in hotel operations. Nevertheless, there are still some absolute criteria of sharia hotels that have not been met by Sofyan Inn Specia Hotel in terms of product, service and managementKey Words: analysis, sharia principles, hotel Sofyan Inn Specia Bandung